Position Synchronization of Electronic Virtual Line Shafting With Sliding Mode Variable Structure Control - Changfan Zhang; Xiao Yuanyuan; Wen Long; He Jing (Institute of Advanced Engineering and Science, 2014)
The degree of precision for positioning of adjustable rollers during pre-registering stage has direct influences on register precision of the entire printing. The paper puts forward control strategy of sliding mode variable structure-based electronic virtual line shafting based on the influences of low-speed pre-register process of shaft-less drive printing press on register precision and the influences of nonlinearity and disturbance on synchronous precision of printing process. It also proves the stability of the control algorithm using Lyapunov function. The experimental results demonstrate that the control strategy proposed by this paper can realize synchronous control of shaft-less drive printing press, and also can inhibit effectively the influences on synchronization of system position due to change of parameters and friction during pre-registering stage.